PENGALAMAN PUSTAKAWAN DALAM MELAKUKAN ANALISIS KEBUTUHAN PENGGUNA LIBRARY EXPERIENCE IN DOING ANALYSIS OF USER NEEDS - YUNUS WINOTO; Sukaesih Sukaesih (BIBLIOTIKA : Jurnal Kajian Perpustakaan dan Informasi, 2020)
Users in collection development activities are very important elements. There are two things that emphasize the user as a central part in collection development activities, the first stage in developing collection must begin with user analysis, secondly almost all stages in collection development require library staff to always see who the user community is. Therefore the research aims to raise the library experience in analyzing user needs. The location of the study was conducted at the library center of IAIN Syeh Nurjati Cirebon. This study uses a quantitative approach to the type of phenomenological research. Data collection techniques are carried out through interviews, observations, and through library studies. As for the data analysis, it is carried out through three stages, namely data reduction, data presentation and data verification. Based on the results of the study note that in the view of librarians of the IAIN library center Syeh Nurjati the user aspect is an element that must be the center of attention in the development of collections, because the purpose of providing collections in the library is to meet user needs. While relating to the experience of librarians in analyzing user needs, it is known that librarians conduct needs analysis both formally and informally. There are several aspects seen in the analysis of user needs, such as the characteristics of library users, curriculum and the implementation of the tri dharma of higher education at IAIN Syeh Nurjati.